An Overview of Tourism Diversity in Nepal - Ghimire, Minesh Kumar (Patan Pragya, 2020)
Tourism is the most important service industry of Nepal. It provided big opportunities of national development and income to maintain international harmony. It will argue the more descriptive nature of information. The diversity of tourism has a huge benefit of tourism development. The tourism activities in Nepal are different attractions such as adventure, natural, cultural etc. The Airway is means of Tourist Arrival means of Nepal and Average Length of Stay is 12 days.